Endometrial Cancer Risk in Women With Germline BRCA1 or BRCA2 Mutations: Multicenter Cohort Study. (12th March 2021) - de Jonge, Marthe M; de Kroon, Cornelis D; Jenner, Denise J; Oosting, Jan; de Hullu, Joanne A; Mourits, Marian J E; Gómez Garcia, Encarna B; Ausems, Margreet G E M; Margriet Collée, J; van Engelen, Klaartje; van de Beek, Irma; et al.
Abstract: Background: Endometrial cancer (EC) risk in BReast CAncer gene 1/2 ( BRCA1/2 ) mutation carriers is uncertain; therefore, we assessed this in a large Dutch nationwide cohort study. Methods: We selected 5980 BRCA1/2 (3788 BRCA1, 2151 gBRCA2, 41 both BRCA1/BRCA2 ) and 8451 non- BRCA1/2 mutation carriers from the Hereditary Breast and Ovarian cancer study, the Netherlands cohort. Follow-up started at the date of the nationwide Dutch Pathology Registry coverage (January 1, 1989) or at the age of 25 years (whichever came last) and ended at date of EC diagnosis, last follow-up, or death (whichever came first). EC risk in BRCA1/2 mutation carriers was compared with 1) the general population, estimating standardized incidence ratios (SIRs) based on Dutch population-based incidence rates; and 2) non- BRCA1/2 mutation carriers, using Cox-regression analyses, expressed as hazard ratio (HR). Statistical tests were 2-sided. Results: Fifty-eight BRCA1/2 and 33 non- BRCA1/2 mutation carriers developed EC over 119 296 and 160 841 person-years, respectively (SIR = 2.83, 95% confidence interval [CI] = 2.18 to 3.65; and HR = 2.37, 95% CI = 1.53 to 3.69, respectively). gBRCA1 mutation carriers showed increased risks for EC overall (SIR = 3.51, 95% CI = 2.61 to 4.72; HR = 2.91, 95% CI = 1.83 to 4.66), serous-like EC (SIR = 12.64, 95% CI = 7.62 to 20.96; HR = 10.48, 95% CI = 2.95 to 37.20), endometrioid EC (SIR = 2.63, 95% CI = 1.80 to 3.83; HR = 2.01, 95% CI = 1.18 to 3.45), and TP53- mutated EC (HR = 15.71, 95% CI = 4.62 to 53.40). For BRCA2 mutation carriers, overall (SIR = 1.70, 95% CI = 1.01 to 2.87) and serous-like EC risks (SIR = 5.11, 95% CI = 1.92 to 13.63) were increased compared with the general population. Absolute risks by 75 years remained low (overall EC = 3.0%; serous-like EC = 1.1%). Conclusions: BRCA1/2 mutation carriers have a two- to threefold increased risk for EC, with highest risk observed for the rare subgroups of serous-like and p53-abnormal EC in BRCA1 mutation carriers.